(untitled) (Journal of research in medical and health sciences, 2025)
The deterioration of skeletal muscle mass and function, termed sarcopenia, is a common metabolic comorbidity in oncology. Contemporary understanding frames its etiology as a multifaceted process driven by tumor-host interactions, extending beyond traditional causes like malnutrition or sedentariness. Malignancies facilitate muscle depletion through the systemic release of inflammatory mediators, dysregulation of protein turnover, and alterations in endocrine function. The resultant sarcopenia subsequently diminishes host immunity and increases the therapeutic burden, creating a challenging clinical feedback loop. This systematic review aims to delineate the epidemiology, pathophysiological mechanisms, and clinical relevance of cancer-related sarcopenia, while also summarizing current and potential future management strategies within a multidisciplinary paradigm.